Trade, technology, and international competitiveness - Ul-Haque, Irfan; Bell, Martin (Washington, D.C. : World Bank, 1995)
"Trade, Technology, and International Competitiveness presents recent thinking in this field and discusses the implications for developing countries.
Includes index.
Includes bibliographical references: p. 197-210.
rpm 08/09/2016
Loans
Keywords: Competition, International; Comparative advantage (International trade).; Technological innovations; BUSINESS & ECONOMICS -- Exports & Imports; BUSINESS & ECONOMICS -- International -- Marketing; BUSINESS & ECONOMICS -- International -- General; POLITICAL SCIENCE -- International Relations -- Trade & Tariffs